ANALISIS STRUKTUR BANGUNAN DENGAN SISTEM STRUKTUR PENAHANAN GEMPA MASONRY - Fitriani, Vira; Ryanto, Muhamad; Sari, Dea Yunita (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Sangga Buana, 2024)
The behavior of buildings with a masonry earthquake resisting system using the Spectrum Response method based on SNI 1726:2019 and 2847:2019, analysis was carried out on structures without walls and brick walls of 3-story buildings that function as residential homes in Jayamandala, South Jakarta. Building in Risk Category II, earthquake priority factor (Ie) is 1, medium soil site class (SD), design spectral 0.626 g and 0.505 g, seismic design category D, site response modification coefficient R for without walls 3 and walls 1 .5. Design period 0.437 seconds, static base shear force in x and y directions without walls 1239.66 kN and walls 2479 kN. The analysis results show that mode 1 without walls is 1.675 seconds and walls are 0.441 seconds, the equivalent shear force in x and y directions without walls is 2284.35 kN and walls is 2478.83 kN, the dynamic earthquake shear force in x and y directions without walls is 2284.36 kN and walls 2479 kN, drift limit drift limit between floors without walls 94 mm and walls 32.9 mm, stress is 45.357 N. Based on the results of structural behavior analysis of masonry earthquake resisting systems, without walls is more flexible than stiffer walls.